Pengaruh Komunikasi Interpersonal, Motivasi Kerja, dan Pengembangan Karir terhadap Kinerja Pegawai Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Bandung - Salfa, Ghaitsa Zahira; Muttaqin, Ridlwan; Rahmi, Palupi Permata (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine the effect of interpersonal communication, work motivation, and career development on employee performance at the Bandung Regency Civil Service and Human Resources Development Agency (BKPSDM). This study was conducted using a quantitative method with a descriptive and verification approach. The questionnaire was distributed to 60 respondents who were samples from a total population of 60 people. The sample in this study was selected using a saturated sampling method. The collected data were analyzed using various statistical methods, including: descriptive analysis, verification, coefficient of determination, and partial and simultaneous hypothesis testing using SPSS software version 26. This study shows that interpersonal communication has a positive and significant impact on employee performance, work motivation has a positive and significant impact on employee performance, while career development does not affect employee performance. However, overall interpersonal communication, work motivation, and career development have a positive and significant effect on employee performance.